Blood-Contacting Biomaterials: In Vitro Evaluation of the Hemocompatibility - Weber, Marbod; Steinle, Heidrun; Golombek, Sonia; Hann, Ludmilla; Schlensak, Christian; Wendel, Hans P.; Avci-Adali, Meltem (Frontiers in Bioengineering and Biotechnology, 2018)
Hemocompatibility of blood-contacting biomaterials is one of the most important criteria for their successful in vivo applicability. Thus, extensive in vitro analyses according to ISO 10993-4 are required prior to clinical applications. In this review, we summarize essential aspects regarding the evaluation of the hemocompatibility of biomaterials and the required in vitro analyses for determining the blood compatibility. Static, agitated, or shear flow models are used to perform hemocompatibility studies. Before and after the incubation of the test material with fresh human blood, hemolysis, cell counts, and the activation of platelets, leukocytes, coagulation and complement system are analyzed. Furthermore, the surface of biomaterials are evaluated concerning attachment of blood cells, adsorption of proteins, and generation of thrombus and fibrin networks.